Reemergence of Sylvatic Dengue Virus Serotype 2 in Kedougou, Senegal, 2020 - Dieng, Idrissa; Diarra, Maryam; Sadio, Bacary Djilocalisse; Sow, Bocar; Gaye, Alioune; Diallo, Amadou; Faye, Martin; Ndione, Marie Henriette Dior; Diallo, Diawo; Sankhe, Safietou; Ndiaye, Mignane; Danfakha, Fode; et al. (Emerging infectious diseases, 2024)
In 2020, a sylvatic dengue virus serotype 2 infection outbreak resulted in 59 confirmed dengue cases in Kedougou, Senegal, suggesting those strains might not require adaptation to reemerge into urban transmission cycles. Large-scale genomic surveillance and updated molecular diagnostic tools are needed to effectively prevent dengue virus infections in Senegal.